2014
DOI: 10.1111/mec.12933
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic stage‐specific quantitative trait loci contribute to divergence in developmental trajectories of sexually dimorphic fins between medaka populations

Abstract: Sexual dimorphism can evolve when males and females differ in phenotypic optima. Genetic constraints can, however, limit the evolution of sexual dimorphism. One possible constraint is derived from alleles expressed in both sexes. Because males and females share most of their genome, shared alleles with different fitness effects between sexes are faced with intralocus sexual conflict. Another potential constraint is derived from genetic correlations between developmental stages. Sexually dimorphic traits are of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 81 publications
2
32
0
Order By: Relevance
“…This shift may be a result of steroid‐dependent gene regulation because the hormonal changes associated with sexual maturation provide a mechanism that could have been co‐opted to change the expression of a specific toxin locus (Kawajiri et al . ), and the shift in phenotype appears to be discrete rather than gradual (Jensen et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…This shift may be a result of steroid‐dependent gene regulation because the hormonal changes associated with sexual maturation provide a mechanism that could have been co‐opted to change the expression of a specific toxin locus (Kawajiri et al . ), and the shift in phenotype appears to be discrete rather than gradual (Jensen et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…; Kawajiri et al . ). The genomewide thresholds of significance of logarithm of the odds ratio (LOD) scores ( P < 0.05) were determined with 1000 bootstrap permutations (genomewide significance threshold of LOD = 3.46).…”
Section: Methodsmentioning
confidence: 97%
“…Reads were trimmed and mapped to the repeat‐masked reference stickleback genome (BROAD S1) using the clc genomic workbench 5.1 with the previously used parameters (Kawajiri et al . , ; Yoshida et al . ) except that the paired‐end distance was set to 10–1000 bp, minimum variant frequency = 0 and required variant count threshold = 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A). QTL and GWAS techniques have also identified seemingly modular age‐specific allelic effects in a wide range of organisms . These studies have all reported that the polymorphisms contributing to trait variation are different at different ages.…”
Section: Genetic Modularity Of Life Histories: the Case For Evolutionmentioning
confidence: 99%